2007
DOI: 10.1080/01674820600999811
|View full text |Cite
|
Sign up to set email alerts
|

Maternal distress and intended breastfeeding duration

Abstract: Early identification of distress in pregnant women and a more attentive encouragement to breastfeed is probably one of the steps to improve intended breastfeeding duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…Likewise, the proposition that reduced maternal selfconfidence and self-esteem is sometimes in the path between SPVP and EBF seems quite tenable. This hypothesis is strengthened by connecting previous findings pointing out that low confidence and feelings of worthlessness are consistent with the long-term psychological consequences of SPVP victimization (38,39) , and with other studies indicating that the psychosocial wellbeing of women during pregnancy is an important protective factor for early weaning (5,(40)(41)(42)(43)(44)(45)(46)(47) . The importance of maternal self-esteem as a mediator of the relationship between SPVP and EBF is also reasonable when comparing the gradual effects of introducing the dimensions in the multivariate model.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Likewise, the proposition that reduced maternal selfconfidence and self-esteem is sometimes in the path between SPVP and EBF seems quite tenable. This hypothesis is strengthened by connecting previous findings pointing out that low confidence and feelings of worthlessness are consistent with the long-term psychological consequences of SPVP victimization (38,39) , and with other studies indicating that the psychosocial wellbeing of women during pregnancy is an important protective factor for early weaning (5,(40)(41)(42)(43)(44)(45)(46)(47) . The importance of maternal self-esteem as a mediator of the relationship between SPVP and EBF is also reasonable when comparing the gradual effects of introducing the dimensions in the multivariate model.…”
Section: Discussionsupporting
confidence: 84%
“…They are unable to perform routine activities of daily living, much less care for the newborn. Thus, it seems unlikely that a mother who lives under conditions of severe violence would find the right environment and, given her own priorities, perhaps the willingness to perform such a demanding task as breast-feeding ( 8 , 34 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms by which maternal stress and distress affect child nutritional status include a less healthy lifestyle, poor psychosocial stimulation of the child and reduced care-seeking for herself and for the child. Patel et al 41 found that depressed mothers in Goa were more likely to have difficulties with breastfeeding or to cease breastfeeding early, and Rondó et al 42 found that distressed women had less intention to breastfeed their children than not distressed women. When weaning, women with stress and distress may be less successful in preparing foods.…”
Section: Discussionmentioning
confidence: 99%
“…Women with chronic infectious diseases, metabolic diseases, cardiopathy, mental diseases, hypertension/pre-eclampsia/eclampsia, vaginal bleeding and multiple deliveries were excluded from the study. Details of the cohort have been published previously (Rondó et al 2003; Rondó & Souza, 2007). …”
Section: Methodsmentioning
confidence: 99%